Obesity promotes oxidative stress and exacerbates blood-brain barrier disruption after high-intensity exercise - Hee-Tae Roh; Su-Youn Cho; Wi-Young So (Elsevier, 2017)
Purpose: The purpose of this study was to investigate the effects of obesity and high-intensity acute exercise on oxidant-antioxidant status, neurotrophic factor expression, and blood-brain barrier (BBB) disruption. Methods: Twenty-four healthy, untrained men (12 non-obese (mean 14.9% body fat) and 12 obese subjects (mean 29.8% body fat)) performed 20 min of continuous submaximal aerobic exercise at 85% maximal oxygen consumption. Blood sampling was performed to examine the oxidant-antioxidant status (reactive oxygen species (ROS) and superoxide dismutase (SOD)), neurotrophic factors (brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF)), and BBB disruption (S100β and neuron-specific enolase) before and after acute exercise. Results: The obese group showed significantly higher pre-exercise serum ROS levels and significantly lower pre-exercise serum SOD levels than the non-obese group (p < 0.05). Serum ROS, SOD, BDNF, NGF, and S100β levels were significantly increased post-exercise compared with pre-exercise levels in both the non-obese and the obese groups (p < 0.05). The obese group showed significantly higher serum ROS, BDNF, NGF, and S100β levels post-exercise compared to the non-obese group (p < 0.05). Conclusion: Our study suggests that episodic vigorous exercise can increase oxidative stress and blood neurotrophic factor levels and induce disruption of the BBB. Moreover, high levels of neurotrophic factor in the blood after exercise in the obese group may be due to BBB disruption, and it is assumed that oxidative stress was the main cause of this BBB disruption.